TINGKAT KEMANDIRIAN, FUNGSI INTEKTUAL DAN STATUS MENTAL LANSIA DI PSWT BUDI MULIA 1 CIPAYUNG JAKARTA TIMUR - Musripah; Sri Laela (Institut Kesehatan Hermina, 2023)
Aging is a process that gradually results in cumulative changes. With increasing age, physiological and psychological functions decrease as a result of the aging process, including: physical decline, memory decline, cognitive decline and depression. The research objective was to determine the level of independence, intellectual function and mental status of the elderly at PSWT Budi Mulia 1 Cipayung, East Jakarta. The research used a quantitative method using a descriptive study design. The sample in this study was 100 respondents, taken by purposive sampling technique. The research was conducted at the Tresna Werdha Budi Mulia 1 Cipayung Institution, East Jakarta. This study used the Bartel Index instrument to assess the level of independence, the Short Portable Mental Status Questionnaire (SPMSQ) instrument to detect the level of intellectual impairment, the Mini mental state examination (MMSE) instrument to assess the presence of cognitive impairment and the Geriatric Depression Scale instrument. The results show that 35% of the elderly are partially dependent, 6% of the elderly are moderately impaired, 8% are mildly impaired, 24% of the elderly are mentally damaged and 84% of the elderly are at risk of depression and 12% of the elderly are mildly depressed. Conclusion in this study: the elderly who live in the Tresna Werdha Cipayung Institution, East Jakarta, are at risk of experiencing depression.